Thyroglobulin autoantibodies switch to immunoglobulin (Ig)G1 and IgG3 subclasses and preserve their restricted epitope pattern after 131I treatment for Graves' hyperthyroidism: the activity of autoimmune disease influences subclass distribution but not epitope pattern of autoantibodies. (7th November 2014) - Latrofa, F; Ricci, D; Montanelli, L; Piaggi, P; Mazzi, B; Bianchi, F; Brozzi, F; Santini, P; Fiore, E; Marinò, M; Tonacchera, M; Vitti, P
Summary: The subclass distribution of thyroglobulin autoantibodies (TgAb) is debated, whereas their epitope pattern is restricted. Radioidine ( 131 I) treatment for Graves' disease (GD) induces a rise in TgAb levels, but it is unknown whether it modifies subclass distribution and epitope pattern of TgAb as well. We collected sera from GD patients before 131 I treatment and 3 and 6 months thereafter. We measured total TgAb, TgAb light chains and TgAb subclasses by enzyme-linked immunosorbent assay (ELISA) in 25 patients. We characterized the TgAb epitope pattern in 30 patients by inhibiting their binding to 125- I Tg by a pool of four TgAb-Fab (recognizing Tg epitope regions A, B, C and D) and to Tg in ELISA by each TgAb-Fab. Total TgAb immunoglobulin (Ig)G rose significantly ( P = 0·024). TgAb κ chains did not change ( P = 0·052), whereas TgAb λ chains increased significantly ( P = 0·001) and persistently. We observed a significant rise in IgG1 and IgG3 levels after 131 I ( P = 0·008 and P = 0·006, respectively), while IgG2 and IgG4 levels did not change. The rise of IgG1 was persistent, that of IgG3 transient. The levels of inhibition of TgAb binding to Tg by the TgAb-Fab pool were comparable. A slight, non-significant reduction of the inhibition by the immune-dominant TgAb-Fab A was observed 3 and 6 months after 131 I. We conclude that 131 I treatment for GD increases the levels of the complement-activating IgG1 and IgG3 subclasses and does not influence significantly the epitope pattern of TgAb. In autoimmune thyroid disease subclass distribution of autoantibodies is dynamic in spite of a stable epitope pattern.